A Comparative Study of Self-concept among Normal Students and Learning Disability Students in Irbid Governorate, Jordan - Bataineh, Osamah; Gawanmeh, Mamoun (Jordan Journal of Educational Sciences, 2005)
The purpose of this study was to investigate the level of selfconcept of normal students and learning disability students in the early elementary stage in Irbid governorate, Jordan. To achieve this purpose, a questionnaire was developed which demonstrated adequate reliability and validity. A sample of (202) student, (119) male and (83) female of normal students and learning disability completed the questionnaire in Irbid governorate during the second semester of 2003-2004. The Results revealed that the level of self-concept among students with learning disability was low; it was lower than that of normal students. The results also revealed that there were no significant differences due to student gender